Analysis and Design of Employee Attendance Applications at the Regional Revenue Service Office of Cirebon Regency - dede sarifah (Institut Pendidikan Indonesia, 2020)
This study contains the analysis and design of attendance applications at the Cirebon district revenue office with the aim of assisting the process of recording employee attendance data at the Regional Revenue Service and minimizing the possibility of fraudulent processes that may occur during absenteeism. The method of analysis and software design used in this paper is 2 stages in the waterfall method according to the pressman which consists of stages of analysis, design, testing, and implementation. The representation of the analysis phase uses a flowmap and data flow diagram, the database design uses an Entity Relationship Diagram (ERD).